Neuropeptide Research in the Eye - Josef Troger (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
The neuropeptide research in the eye is the main topic of our scientific group in Innsbruck. Most of the neuropeptides have been discovered more than 30 years ago and the presence and distribution of some of them has been explored in the eye in the 80´s mainly by Richard Stone. This concerns particularly substance P (SP), calcitonin gene-related peptide (CGRP), vasoactive intestinal polypeptide (VIP) and neuropeptide Y (NPY). Whereas SP and CGRP have been found to be constituents of the sensory innervation of the eye, VIP is present in the parasympathetic and NPY in the sympathetic innervation of the eye. These results have been reviewed in 1987 in "Experientia". In the retina, the typical neuropeptide localization are amacrine cells in the proximal inner nuclear layer and displaced amacrine cells in the ganglion cell layer but some of them are also present in ganglion cells. As mentioned above the flowering time of the neuropeptide research in the eye were the 80´s because everyone believed that these are novel neurotransmitters apart from the catecholamines, acetylcholine and certain amino acids. But it came apparent that these are rather neuromodulators and probably because of this reason the interest in neuropeptide research decreased in the last three decades. However, the innervation of the eye by several further peptides has been explored including galanin, somatostatin, cholecystokinin, nitric oxide, pituitary adenylatecyclase (PACAP) and neurokinin A and the results of these explorations have been reviewed in the year 2007 by our scientific group in Innsbruck in "Brain Research Reviews" and in the book "Neuropeptides in the eye" which has been released in 2009 in "Research Signpost".